PENDAMPINGAN GURU DALAM MENGEMBANGKAN MODUL AJAR BERBASIS EXPERIENTIAL LEARNING PADA SATUAN PAUD - Dhian Gowinda Luh Safitri; Yes Matheos Lasarus Malaikosa; Sri Setyowati; Mallevi Agustin Ningrum (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
Teacher training is an important strategy for improving the quality of early childhood education particularly in implementing learning approaches that emphasize meaningful experiences. This article aims to describe the evaluation results of an Experiential Creative Learning module training for early childhood education teachers and to examine teachers’ understanding expectations implementation challenges and the initial impact on classroom practices. The training was conducted in Temanggung Regency and involved 30 teachers from playgroup and kindergarten levels who are members of HIMPAUDI. A descriptive approach was employed with data collected through post training evaluation questionnaires. The findings indicate that most teachers demonstrated a good level of understanding of the Experiential Creative Learning concept after participating in the training. Teachers expressed expectations that learning activities would become more meaningful interactive and capable of encouraging children’s active participation and creativity. However several challenges were identified including limited time workload demands shifts in teacher mindset and insufficient institutional and facility support. These findings suggest that Experiential Creative Learning training has the potential to strengthen meaningful learning practices in early childhood education although sustained mentoring and systemic support are necessary to ensure long term implementation.